Factors associated with inconsistent condom use among young people: systematic review - Rafael de Siqueira Silva; Pedro Augusto Bossonario; Melisane Regina Lima Ferreira; Rubia Laine de Paula Andrade; Rafaele Oliveira Bonfim; Vitória Alencar; Aline Aparecida Monroe (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To identify in the literature the factors associated with the inconsistent use of conservation by the young population. Method: Systematic review that searched for studies in six data sources in June 2023, with no publication date or language restrictions. Materials were selected by two independent reviewers who individually screened observational studies by reading the title and abstract of the articles. The studies were assessed for methodological quality and narrative synthesis. Results: Of the 15,783 publications retrieved, nine were included. It was found that anal sex, not carrying a condom, low education, shame about buying condoms, drug use, early sexual debut and difficulties in negotiating condom use were factors associated with inconsistent condom use among the young population. Conclusion: Multidimensional factors are associated with inconsistent condom use, permeated by sociodemographic, cultural and behavioral elements that challenge practices and policies aimed at promoting sexual and reproductive health, including the control of sexually transmitted infections.